OPTIMALISASI PEMBERDAYAAN PEREMPUAN DALAM KEPEMIMPINAN EFEKTIF - Astuti, Rini Puji (LP2M IAIN Jember, 2019)
The challenge in dealing changes and demands in coming era is the rapid change of dynamic times. So that, the role of women is needed in dealing an existing problems in society, such as many social problems that occur in the society. therefore, need a leader who is reliable and resilient. Today, women's leadership is still being debated because some Muslim societies are viewed cynically, even though it has long been found that women have succeeded in being the subject of achieving leadership goals, for example in development, so the term